2017
DOI: 10.1051/parasite/2017001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofCryptosporidiuminfection in cattle in China: a review

Abstract: The present review discusses the findings of cryptosporidiosis research conducted in cattle in China and highlights the currently available information on Cryptosporidium epidemiology, genetic diversity, and distribution in China, which is critical to understanding the economic and public health importance of cryptosporidiosis transmission in cattle. To date, 10 Cryptosporidium species have been detected in cattle in China, with an overall infection rate of 11.9%. The highest rate of infection (19.5%) was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 44 publications
(89 reference statements)
11
64
3
1
Order By: Relevance
“…The results of C. bovis and C. ryanae corroborate the review of 16 papers of Gong et al (2017) who performed molecular methods. The authors concluded that C. ryanae affects animals from birth through eight weeks of life; however, C. bovis can also affect animals of 12 weeks old (SANTÍN et al, 2004).…”
supporting
confidence: 83%
“…The results of C. bovis and C. ryanae corroborate the review of 16 papers of Gong et al (2017) who performed molecular methods. The authors concluded that C. ryanae affects animals from birth through eight weeks of life; however, C. bovis can also affect animals of 12 weeks old (SANTÍN et al, 2004).…”
supporting
confidence: 83%
“…The LOD of the assay described herein falls between 7 and 29 parasites per microliter (Table 2 ) and is therefore similar to those reported for conventional PCR assays. Rapid diagnostic tests for detection of malaria antigens are typically less sensitive and are reportedly most suitable for detecting parasitemias above 200 parasites per microliter [ 29 ]. Meanwhile, for Plasmodium species, it is estimated that a highly competent microscopist can detect approximately 50 parasites per microliter of blood [ 30 ] while a typical microscopist using the WHO standardized method detects an average of 88 parasite per microliter [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…is a recent development in China (Chen and Huang, 2007 ; Wang et al, 2008a , b , c ), genotyping and subtyping tools are now widely used in the characterization of Cryptosporidium spp. in various animals (Karim et al, 2014 ; Liu et al, 2014a , b , 2015a , b ; Ma et al, 2014 , 2015 ; Qi et al, 2014 , 2015a , b , d , 2016 ; Wang L. et al, 2014 ; Ye et al, 2014 ; Zhao et al, 2014 ; Du et al, 2015 ; Li J. et al, 2015 , 2017 ; Liu A. et al, 2015 ; Li W. et al, 2015 , 2017 ; Qi, M. Z., et al, 2015 ; Wang et al, 2015a , b ; Zhang et al, 2015a , b ; Zhao G. H. et al, 2015 ; Zhao Z. et al, 2015 ; Jian et al, 2016 ; Li F. et al, 2016 ; Li P. et al, 2016 ; Li Q. et al, 2016 ; Peng et al, 2016 ; Taylan-Ozkan et al, 2016 ; Xu et al, 2016 ; Yang et al, 2016 ; Zhang S. et al, 2016 ; Deng et al, 2017 ; Gong et al, 2017 ; Zou et al, 2017 ). The use of molecular diagnostic tools in prevalence studies has led to the identification of significant differences in the transmission of Cryptosporidium spp.…”
Section: Molecular Epidemiologic Toolsmentioning
confidence: 99%